Magnesium-Catalyzed N2-Regioselective Alkylation of 3-Substituted Pyrazoles - Xu, Di; Frank, Lena; Nguyen, Tina; Stumpf, Andreas; Russell, David; Angelaud, Remy; Gosselin, Francis (Synlett, 2020)
A highly regioselective Mg-catalyzed alkylation of 3-substituted pyrazoles has been developed to provide N2-alkylated regioisomers. Using α-bromoacetates and acetamides as alkylating agents, this new method was applied to a variety of 3-substituted and 3,4-disubstituted pyrazoles to produce the N2-alkylated products with high regioselectivities ranging from 76:24 to 99:1 and 44–90% yields.
Keywords: pyrazole; alkylation; magnesium; catalysis; regioselectivity